Zāhirah al-Du’a al-Musytarak baina al-Mutadayyinīn bi Indonesia: Nazrah min Manzur al-Islām (Journal of Comparative Study of Religions, 2023)
This article examines the practice of interfaith prayers and Islamic perspective of it. The phenomenon of interfaith prayers in Indonesia is a result of the widespread understanding of religious pluralism propagated by liberals in this country. After a deeper examination using critical analysis, it is found that such prayers cannot be justified and are not acceptable to sound reason and true faith. Each religious community participating in joint prayers has their own diverse concepts of God, and each of them has their distinct ways to depict their deity and specific methods of expressing their prayers. Hence, it is highly improbable to reconcile these differences within a single religious ritual that is attended by various diverse religious communities. Interfaith prayers are a part of religious pluralism, as in these prayers, participants are compelled to believe in the legitimacy of prayers from other religious communities, indirectly validating the gods of different religions, despite their varying understanding of the divine. This contradicts the teachings of Islam and the Islamic creed. Islam firmly believes that truth lies solely in Islam, the teachings brought by Prophet Muhammad (peace be upon him) as the seal and completion of the teachings of all the prophets and messengers before him. Therefore, there is no salvation except through Islam, and believing in the truth of other religions amounts to believing in their gods, which is considered a grave sin of polytheism (shirk).